Monopolistic Competition and Entrepreneurial Risk-Taking - Too many Cooks Spoil the Broth (but Everyone is better off) - - Christiane Clemens (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
This paper investigates the effects of monopolistic competition on entrepreneurial risk-taking in a general equilibrium model. In this context, occupational choice of risk averse agents is biased towards firm ownership. In this case, the inefficiencies due to the presence of non-diversifiable risk are partly compensated by inefficiencies arising from imperfect competition. Comparative static results show that too many firms remain in the market for an increase in the degree of risk aversion, thereby mutually deteriorating profit opportunities, which provides an explanation for the empirically observed comparably low risk premium on entrepreneurial risk.
Keywords: D4; D5; D8; 330; economics of uncertainty; occupational choice; monopolistic competition; Monopolistischer Wettbewerb; Unternehmer; Risikopräferenz; Theorie